Development of Cloud-Connected Smart Home Control System Using Esp32 and Relay Module - Muhammad Erpandi Dalimunthe (INFOKUM, 2025)
The rapid growth of the Internet of Things (IoT) has enabled the integration of smart energy management systems into residential environments, allowing users to remotely control and monitor household electrical devices in real time. This paper presents the development of a cloud-connected smart home control system using the ESP32 microcontroller and a relay module as the switching interface for electrical appliances. The system is designed to optimize energy efficiency and power consumption through the implementation of wireless control via Wi-Fi and real-time data synchronization with a cloud server. The development of Internet of Things (IoT) technology provides a great opportunity in creating a smart and efficient home automation system. This study discusses the design and implementation of a household device control system using an ESP32 microcontroller integrated with a relay module as a controller for electrical loads such as lights and fans. The main objective of this study is to design a prototype of an IoT-based control system that can be operated via a Wi-Fi network and controlled using a smartphone application. The research method includes hardware design (ESP32, relay module, and electrical load), software design (user interface and connection to the Blynk platform), and system testing for response speed and communication stability. The test results show that the system can control devices with an average response time of 0.42 seconds, and a communication success rate of 98.7%. The results of this study prove that the use of ESP32 and relay modules as an IoT-based control system can be applied effectively for household automation, and become the basis for the development of smart homes in the future.